SONOGRAPHIC AND DOPPLER EVALUATION OF CAROTID ARTERY IN HYPERTENSIVE PATIENTS - A CORRELATIVE STUDY WITH BIOCHEMICAL PARAMETERS - Remya R.; Sai Shankar Mankuzhy Gopalakrishnan; Nillohit Saha; Harshavardhan Balaganesan; Jenikar Paulraj (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Hypertension is a major contributor to cardiovascular disease having a multiplicative effect on atherosclerosis, which basically implies an increase in Intima-Media Thickness (IMT). Duplex sonography can be used to assess the carotid artery, which is a combination of high-resolution greyscale imaging and Doppler analysis. Purpose: To evaluated carotid artery characteristics using high quality grayscale ultrasound and doppler in patients with hypertension and correlated with biochemical parameters. Method: A cross-sectional study was conducted among 135 hypertensive patients (aged ≥50), who were stratified by the severity of their hypertension. Grayscale (IMT, plaque assessment) and doppler (RI, resistive index) measures of both Common Carotid Arteries (CCA) were acquired along with different parameters of blood pressure (SBP, DBP, MBP) and lipid profiles (TC, TG, LDL, HDL). Data analysis was done with SPSS 21. Result: Out of 135 patients, 79 (58.5%) were in subgroup I and 56 (41.5%) in subgroup II, with equal gender distribution. IMT values were higher in subgroup II (0.741±0.013) than subgroup I (0.725±0.017 and 0.731±0.019). SBP correlated significantly with IMT and RI, while DBP, MBP, and cholesterol had no significant correlation with IMT. Doppler RI showed a moderate correlation with DBP and MBP. Triglycerides, LDL, and HDL had no significant correlation with IMT or RI. Conclusion: Ultrasound is a rapid, safe, and cost-effective tool for detecting atherosclerosis. The combined evaluation of IMT and RI using grayscale ultrasound and doppler may detect early atherosclerotic changes.